Characterization of Soybean STAY-GREEN Genes in Susceptibility to Foliar Chlorosis of Sudden Death Syndrome. Issue 2 (5th April 2019) - Chang, Hao-Xun; Tan, Ruijuan; Hartman, Glen L.; Wen, Zixiang; Sang, Hyunkyu; Domier, Leslie L.; Whitham, Steven A.; Wang, Dechun; Chilvers, Martin I.
Abstract : Genetic mappings for soybean sudden death syndrome foliar chlorosis suggested that STAY-GREEN genes with loss-of-susceptibility mechanism may have different breeding merits for disease resistance.